Visible light photoacoustic ophthalmoscopy and near-infrared-II optical coherence tomography in the mouse eye - Haindl, Richard (2024)
Non-invasive imaging plays a crucial role in diagnosing and studying eye diseases. However, existing photoacoustic ophthalmoscopy (PAOM) techniques in mice have limitations due to handling restrictions, suboptimal optical properties, limited availability of light sources, and permissible light fluence at the retina. This study introduces an innovative approach that utilizes Rose Bengal, a contrast agent, to enhance PAOM contrast. This enables visualization of deeper structures, such as the choroidal vasculature and sclera in the mouse eye, using visible light. The integration of near-infrared-II (NIR-II) optical coherence tomography provides additional tissue contrast and insights into potential NIR-II PAOM capabilities. To optimize imaging, we developed a cost-effective 3D printable mouse eye phantom and a fully 3D printable tip/tilt mouse platform. This solution elevates PAOM to a user-friendly technology, which can be used to address pressing research questions concerning several ocular diseases, such as myopia, glaucoma, and/or age-related macular degeneration in the future.